From Obsolescence to Sustainability: Exploring University Students’ Preference on the Lifetime of Devices - Adhenz M. Miranda; Iftikhar Alam Khan; Arshiya Subhani; Usman Ahmad; Rafia Muhammad Murtaza (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study investigates university students’ electronic device consumption behaviors, focusing on sustainability awareness, device obsolescence perceptions, and purchasing decision factors. A quantitative survey was conducted among university students, utilizing a Likert scale to assess attitudes towards device usage, sustainability, and upgrade decisions. The research employed descriptive statistical analysis to examine factors influencing device consumption. Results revealed performance specifications (4.47/5) and durability (4.43/5) as primary purchase drivers. Students demonstrated moderate environmental awareness (3.58/5) but showed a strong preference for new devices (82.6%) over refurbished options (17.4%). The average laptop age was 3.06 years, with students expecting devices to remain functional for 5.22 additional years. The study provides unique insights into the disconnect between environmental awareness and actual device consumption behaviors among university students, highlighting the complex interplay between technological expectations and sustainability considerations. The findings suggest a need for targeted educational interventions, marketing strategies, and policy recommendations to bridge the gap between environmental consciousness and device purchasing decisions.